MANAJEMEN HAJI DAN UMRAH DALAM PEMETAAN BIBLIOMETRIK - Mansyur, Abdurrahman; Hudaya, Nurul (Institut Agama Islam Negeri Metro, 2023)
This research aims to analyze research trends in the field of Hajj and Umrah management from researchers around the world. Through bibliometric analysis, this research provides an overview of research maps formed from keywords and important issues analyzed using the VOSviewer application. Data was obtained from the Dimensions.ai database, with the search keyword